Stem cell biology and neurodegenerative diseases - McKay, Ronald (Henry Stewart Talks, 2007)
Types of stem cells: embryonic or pluripotent, somatic, fetal vs. adult, Are stem cells a threat or a benefit?, Neurons are molecularly complex, Stem cells in the developing brain, Stem cells in the blood, Stem cells and plasticity, Stem cells make real neurons, Controlled differentiation of stem cells, Neurodegenerative diseases and use of stem cells